(untitled) (Castilla. Estudios de Literatura, 2013)
The present article joins in the contemporary debate about the reactivation of the classical rhetoric as discourse theory, by going deeper in an investigation field which has been explored, up to now, indirectly and not systematically: figurativity of fictional narrative. In line with this objective, it proposes a macro-structural and extensive conception of figure, by understanding macrofigures as devices that go beyond the sentence and operate, within more extensive textual segments, on a narrative level, i.e, in the syntax and semantics of narration, not of sentence. By considering the complexity of some decisive theoretical issues (logical distinction between metaphorical and metonymic processes; difference between diegetic and non-diegetic figures; operative definition of rhetorical figure as a device respect to a theoretical “zero degree” of story), this article examines some rhetorical figures that showed themselves to be very productive in narrative fiction (metaphor, metonymy, hyperbole, ellipsis, inversion, repetition, antithesis, allegory, paradox, preterition, freudian negation [Verneinung]) and illustrate its way of working through examples extracted from Alfred Döblin’s novel ‒exemplary as regard her rhetorical structure‒ Berlin Alexanderplatz.